Country Economic Memorandum : Realizing the Development Potential of Lao PDR, Volume 2. Main Report - World Bank (Washington, DC, 2013)
To sustain or exceed the 1990s annual average growth rate of 6.3 percent, Lao will need to promote agricultural and manufactured exports, and increase the contribution of natural resources to development. This will require another round of reforms, and supportive public spending. These reforms should seek to create a more enabling environment for the private sector, and for exports, to raise revenue and maintain macroeconomic stability, as well as to improve the transparency, accountability and efficiency of public expenditure management, and public service delivery. To develop natural resources and mineral reserves, Lao will need to attract substantial international and domestic capital to meet the heavy front-end capital costs required to exploit mineral deposits. To bring in that investment, however, requires improvement in governance of the mining sector, particularly in regard to partnerships with the private sector. Looking specifically at growth and poverty reduction, three scenarios for growth - base, base plus and high - show aggregate GDP growth up to 2015, rising roughly by an annual average of 4-5 percent, 5-6 percent, and 6-8 percent respectively. These indicate that this long-term growth will be driven largely by manufacturing (industry) and services, with growth from agriculture though important in the initial years, its contribution declining in the long-term. These growth scenarios depend very much on the pace and depth of reforms the country implements. Additionally, rising government revenues from natural resources alone will not suffice to meet social needs. On current trends, for example, per capita recurrent expenditures in health hardly increase until 2015. The country will need to take additional revenue measures and reallocate expenditures to increase recurrent expenditures on social sectors. To be effective, such revenue and expenditure measures must also be accompanied by efficient improvements in the service delivery mechanisms, i.e., increasing the participation of the poor.